Pravilnik za opis i pristup građi u knjižnicama, arhivima i muzejima - Vukadin, Ana (Knjižnica, 2019)
Purpose: In this article we present the on-going project Production, Publishing and Maintenance of the National Cataloguing Rules aimed at harmonizing cataloguing practices in the Croatian libraries, archives and museums within a common content standard - Rules for Description and Access to Resources in Libraries, Archives and Museums. The project started in 2013 when the representatives of the three heritage communities and the academic community signed the Agreement of collaboration on the design of national cataloguing rules. Ministry of Culture of the Republic of Croatia has been financially supporting the project since 2014. The project is scheduled to end 2019 with the publication of the first standard version of the Rules. Methodology/approach: The article describes the conceptual models IFLA LRM (Library Reference Model), CIDOC CRM (Conceptual Reference Model) and ICA RiC (Records in Contexts), their grounding in the linked data technology and the Semantic Web standards (LOD: linked open data and RDF: Resource Description Framework), and their application in the development of the Rules. It provides the description of the purpose and goals, use, principles and structure of the Rules, focusing on the unit of description (resource), and discussing the solutions derived from the application of the mentioned models and other international standards. Results: The project has demonstrated the feasibility of successful collaboration between heritage institutions and the academic community on the development of unified cataloguing rules. The common data elements mandatory for the identification of resources have been recognized and combined with those specific to the type of the resource and its function within a particular institution or collection. The cataloguing terminology has been updated and harmonized. Research limitations: The Rules are still in the process of development. The parts of the text that have been adopted by the Programme Committee of the project, but not yet integrated into the Rules, regard the identification and description of the agent, place and time-span, the relationships between entities, the appendices and the glossary. Originality/practical implications: The article presents the methodology used in the development of cataloguing rules for heterogeneous information environment and based on the internationally adopted principles, models, standards and guidelines for various types of resources, as well as on new technologies of the Semantic Web. The Rules, being the ontology of the HR-KAM domain, can be used as a cataloguing code, a set of guidelines for registration and documentation of cultural heritage collections, a datamodel for the design or updating of information systems or databases, an ontology for data publishing, exchange (interoperability) and integration (re-use), and a searching tool for different data sources.
Keywords: arhivsko gradivo; Hrvaška; katalogizacija; katalogizacijska pravila; knjižnično gradivo; pravilniki